2019
DOI: 10.1017/s0022215119001300
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of ossiculoplasty using bone cement

Abstract: ObjectiveThis study aimed to evaluate the long-term results of ossiculoplasty using bone cement.MethodForty patients (24 females and 16 males; mean age: 34.1 ± 11.8 years; range, 9–54 years) with chronic otitis media with perforation but without cholesteatoma who had undergone incudostapedial rebridging ossiculoplasty using bone cement were evaluated retrospectively. Pre-operative and post-operative audiograms were evaluated. Bone conduction, air conduction and air–bone gaps were calculated according to intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Since we could not see a publication describing this modification in the literature, we needed to share the results of this modified technique. While reconstructing the incudostapedial bridge, we used bone cement that proven success and easily applicable [14][15][16] . Due to the risk of absorption and dislocation with the material made with bone or cartilage, we use bone cement very often in our clinic in order to minimalize the failure in ossiculoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we could not see a publication describing this modification in the literature, we needed to share the results of this modified technique. While reconstructing the incudostapedial bridge, we used bone cement that proven success and easily applicable [14][15][16] . Due to the risk of absorption and dislocation with the material made with bone or cartilage, we use bone cement very often in our clinic in order to minimalize the failure in ossiculoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Also our results with endoscopic modified butterfly tympanoplasty were similar to those in previous studies. For 15 . In another study performed by Güngör et al, an ABG gain of 13 dB was reported in 30 patients who underwent incudostapedial reconstruction 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers consider that the most crucial factors affecting the long-term outcome of ossiculoplasty are persistent middle ear disease such as cholesteatoma, atelectasis, and Eustachian tube dysfunction. Such factors are often indications for reoperation and, as a consequence, worse hearing results [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…Die Verwendung von Zement ist eine elegante Lösung mit zuverlässiger Ankopplung. In einer Studie an 40 Patienten und einer Nachbeobachtungszeit von 4 Jahren reduzierte sich der ABG von 27,65 dB auf 19,65 dB und liegt damit in der Größenordnung der Winkelprothese [24]. Bei Kindern wurde das Re-Bridging mit der Interposition verglichen, wobei der Hörgewinn in der Ionomerzementgruppe signifikant besser war als nach Interposition des Ambosses [25].…”
Section: Rekonstruktion Der Ossikelketteunclassified